Los primeros años de Trabajo, el periódico del Partido Comunista de Costa Rica (1931-1935) - Iván Molina Jiménez (Amnis)
This paper analyzes the political and financial difficulties of Trabajo, the weekly newspaper of the Communist Party of Costa Rica, during its first years of publication (1931-1935). It is argued that Trabajo played a central role in supporting the union and electoral activities of the Party, and it simultaneously contributed to legitimize social change by the way of reform.